The Locus Standi of Heirs in Claiming Matrimonial Property (Jointly Acquired Property) After Death Among Muslims in Malaysia - Ahmad, Md Yazid; Hasbullah, Badriah; Herlindah, Herlindah; Permadi, Iwan (El-Usrah: Jurnal Hukum Keluarga, 2025)
The right to claim matrimonial property (jointly acquired property) is an exclusive entitlement of the husband or wife that could be pursued in the event of a divorce, polygamy, death or conversion to another religion. In cases where such claims arise following a death of either spouse, the Syariah Court has allowed heirs to continue the claim for matrimonial property on behalf of the deceased, provided that the deceased had initiated such a claim while the deceased was still alive. However, complications arise when heirs attempt to file such claims even though the deceased never pursued any claim during the deceased’s lifetime. This article explores the legal standing, or locus standi, of heirs who adduce claims on matrimonial property after the death of a relative, based on Syariah Court decisions in Malaysia. This qualitative study employed document analysis, presented descriptively through the case study methodology, involving Syariah Court proceedings. Findings indicate that, in principle, heirs, other than the husband or wife who is still living, do not automatically possess the legal standing to claim matrimonial property on behalf of the deceased, as they do in matters of inheritance under Islamic estate law, unless the deceased had explicitly delegated such authority to them. Nonetheless, it is essential to first determine why eligible parties had failed to file the claim during their lifetime. Given the absence of clear textual evidence from Islamic sources, either permitting or prohibiting such claims by heirs, and the lack of specific provisions addressing this issue in state-enacted Islamic family law, judges have exercised their discretion in varying ways when deciding these cases.